Improving students’ mathematics learning outcomes through the implementation of think-pair-share model - Sitti Rahmah Tahir; Muhammad Irfan Basri; Andi Mulawakkan Firdaus (Universitas Islam Negeri Maulana Malik Ibrahim, 2019)
This research is a classroom action research which aims to improve mathematics learning outcomes through the application of the Think-Pair-Share type of cooperative learning model. The research subjects were 25 tenth grade students who consisted of 9 male students and 16 female students. The instruments used were observation sheets, response questionnaires, and learning outcomes tests. Data collection techniques in this study were information on student activities, implementation of actions, and students’ learning outcomes. Data on the observations of student activities and response questionnaires will be analyzed qualitatively, whereas data on students’ learning outcomes will be analyzed quantitatively using descriptive statistics. The results of this study showed that the application of the cooperative learning model with Think-Pair-Share model can improve students’ mathematics learning outcomes.